Effect of the duration of oil fractions electrocracking on the output and characteristics of the products formed - A. I. Nikolaev; B. V. Peshnev; N. N. Trofimova (Тонкие химические технологии)
The article presents the results of studies on the effect of oil raw material electrocracking duration on the characteristics of the products formed. It is shown that an increase in the duration of the decomposition of the material leads to an increase in the concentration of acetylene in the gas, a higher content of aromatic hydrocarbons and the molecular weight of the liquid phase, a higher degree of structure of soot and reduction of its sorption characteristics.